Comparative study of azathioprine and cyclosporin in rheumatoid arthritis â a sixteen weeks follow-up study (Medical Journal of Indonesia, 2002)
Rheumatoid Arthritis (RA) is a chronic progressive deforming polyarthritic disease involving multisystems and associated with considerable morbidity. Immunosuppressive drugs have been used to reduce/arrest the progression of the disease. The present study was undertaken to compare the efficacy of Azathioprine and cyclosporin in Rheumatoid Arthritis patients. Study consisted of 100 patients of Rheumatoid Arthritis (as per criteria of American Rheumatism Association, 1987) divided into two groups : group I received Azathioprine 1 mg/kg/d and group II received cyclosporin 2.5-3.0 mg/kg/d for 16 weeks. Assessment of efficacy was based on clinical, biochemical and radiological parameters. All patients showed marked improvemen (p value < 0.001) in all clinical parameters i.e. relief in pain, reduction in morning stiffness, painful/swollen joint along with walking time for 50 feet and increase in grip strength. All patients showed reduction (p < 0.001) in ESR without any change in rheumatoid factor titres. Both drugs showed equal efficacy (p value = NS) in improvement of clinical and biochemical parameters. But cyclosporin showed more reduction in bony erosions and juxtaarticular osteoporosis. Ten patients showed nephrotoxicity with cyclosporin. Cyclosporin has an edge over azathioprine in reducing the rate of progression of joint change in Rheumatoid Arthritis but is associated with increased incidence of side effects that are generally manageable. (Med J Indones 2002; 11: 153-7) Keywords: azathioprine, cyclosporin, rheumatoid arthritis